Pengaruh Limbah cair Home Industry Batik terhadap kemampuan Echinodorus radicans - Irssa Intan Fatiha; Rony Irawanto (Gunung Djati Conference Series, 2021)
Batik industrial wastewater is the most produced waste and has the potential to pollute the environment if it is not managed properly. The batik industry, which mostly uses water, will produce heavy metal liquid waste in the form of Pb, Cu, Cd, Zn, Cr. One of the management efforts that can be done is with phytoremediation which is the use of plants to remove pollutants from contaminated water. Aquatic plants besides having aesthetic value also have ecological value in restoring environmental quality(phytoremediation) due to water pollution. The aquatic plant used in this study is Echinodorus radicans. This research is experimental to determine the initial concentration of phytoremediation. The purpose of this study was to determine the effect of batik liquid waste on changes in pH, temperature and morphology (stems and leaves) of Echinodorus radicans in reducing Pb and Cu levels during the phytoremediation process. This research was conducted at the Purwodadi Botanical GardensPlant Conservation Center-LIPI from March 25 to April 7, 2021. This study used 4 variations of concentration consisting of 0 ppm,1 ppm, 3 ppm, and 5 ppm. The result of giving the home-industry batik liquid waste is that it has no effect on the growth of plant stems and leaves, but a decrease in temperature and pH except at 0 ppm (control).